Down-regulation of EZH2 expression in myelodysplastic syndromes. (May 2016) - Cabrero, Monica; Wei, Yue; Yang, Hui; Ganan-Gomez, Irene; Bohannan, Zach; Colla, Simona; Marchesini, Matteo; Bravo, Guillermo Montalban; Takahashi, Koichi; Bueso-Ramos, Carlos; Garcia-Manero, Guillermo
Highlights: EZH2 expression is frequently reduced in MDS. EZH2 expression is associated with chromosome 7 abnormalities. EZH2 underexpression and KDM6B overexpression affect innate immune gene expression. Abstract: EZH2 genetic mutations are common in myelodysplastic syndrome (MDS), which implies that this gene has a pathophysiological role in the disease. To further characterize molecular alterations of EZH2, and their potential prognostic impact in MDS, we assessed EZH2 RNA expression in primary bone marrow CD34+ cells from 78 patients. We found that 47% of patients have reduced EZH2 expression compared to normal controls. Further analyses revealed that EZH2 is significantly underexpressed in patients bearing chromosome 7 or 7q deletions (7-alt) when compared to controls, diploid patients, and patients with other cytogenetic alterations ( p  < 0.05). In survival analysis, we found a non-significant trend toward overall survival (OS) being better among patients with EZH2 underexpression (median OS 55 vs. 36 months; p  = 0.71). Importantly, this trend became significant when the analysis was restricted to the subset of cases without alterations in chromosome 7 (62 vs. 36 months; p  = 0.033). Furthermore, our previous work has identified a spectrum of innate immune genes in MDS CD34+ cells that are deregulated via abnormal promoter histone methylation. Because EZH2 is a key regulator of histone methylation, we assessed the relationship between deregulation of these genes and EZH2 underexpression. We observed that the mRNA levels of 11 immune genes were higher in the EZH2 underexpression group and that immune gene expression was significantly higher in patients with concomitant EZH2 underexpression and KDM6B (also known as JMJD3, an H3K27 demethylase) overexpression. Taken together, these data indicate that EZH2 underexpression may have unique impact on the molecular pathogenesis and prognosis in MDS and be an important marker for patients without chromosome 7 alteration.